L1CAM expression in colorectal cancer identifies a high-risk group of patients with dismal prognosis already in early-stage disease. (2nd January 2020) - Tampakis, Athanasios; Tampaki, Ekaterini Christina; Nonni, Afroditi; Tsourouflis, Gerasimos; Posabella, Alberto; Patsouris, Efstratios; Kontzoglou, Konstantinos; von Flüe, Markus; Nikiteas, Nikolaos; Kouraklis, Gregory
Abstract: Background: Metastatic disease in colorectal cancer represents a major cause of significant cancer-associated morbidity and mortality. L1CAM is a stem cell marker, cell adhesion molecule, belongs to the immunoglobulin superfamily of cell adhesion molecules (IgCAM) and it is aberrantly expressed in several different types of human solid tumors. The aim of the present study was to assess the expression patterns of L1CAM and its clinical significance in colorectal cancer. Patients and methods: Surgical specimens of 109 patients with primary resectable colorectal cancer were examined for L1CAM expression via immunohistochemistry and the results were correlated with clinical and survival data. Results: L1CAM expression was significantly correlated with advanced stage of disease ( p < .001), higher T classification ( p = .040), the presence of lymph node ( p < .001) and distant metastasis ( p = .011). Patients displaying high L1CAM expression demonstrated a dismal three-year progression free survival (29.7% vs 87.1%, p < .001) and five-year overall survival (39.9% vs 87.7%, p < .001). Multivariate analysis using Cox proportional hazard models revealed high L1CAM expression as a prognostic marker of dismal progression free (HR 0.187, 95%CI = 0.075–0.467, p < .0001) and overall survival (HR 0.154, 95%CI = 0.049–0.483, p = .001) independent of other clinicopathological characteristics. Subgroup analysis comprised of patients with early stage disease only presented as well significantly worse progression free and overall survival when L1CAM exhibited high expression. Conclusions: Colorectal cancer patients displaying high expression of L1CAM harbor high risk for metastasis already in early stage disease identifying therefore a group of patients prone to dismal prognosis.